How certain are we about the role of uncertainty in the economy? - Helmut Herwartz; Alexander Lange (Economic Inquiry, 2023)
While causes and consequences of uncertainty in the US economy have attracted viable interest, the literature still lacks a consensus on several aspects. To name two matters of debate, it remains unclear whether uncertainty shocks are a source or the result of recessions and whether uncertainty shocks have adverse (or even stimulating) effects on the economy. We find that ambiguous results in these regards can be traced back to the selection of an appropriate identification strategy in structural vector autoregressive models. We find that both macroeconomic and financial uncertainty are exogenous to business cycle fluctuations and cause economic slowdowns.
Keywords: 330; heteroskedasticity; independent components; model selection; non-Gaussianity; structural vector autoregression; uncertainty shocks